1990
DOI: 10.3758/bf03205318
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of an old memory during sleep and wakefulness

Abstract: In aseries of four experiments, the effects of the reactivation of an old memory in different states of vigilance were investigated. Rats were trained to run in a six-unit spatial discrimination maze for food reward with low-Ievel electrical stimulation delivered to the ear when they entered blind alleys. Twenty-five days after training, electrotactile stimulation was given to animals as a reactivating treatment just before a retention test. When the cuing treatment was given during wakefulness, retention perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The delivery of the mild ear-shock was ineffective when the food-shock had been associated with a tone (rather than a mild ear-shock) at training, excluding unspecific effects of stimulus presentation during sleep. Cueing during waking did not affect learning, whereas cueing during SWS and also cueing of old, remote memories during REM sleep acquired 25 days before reduced fear memories (517,518), indicating that cueing of fear memories during sleep strengthen these memories only when cueing is conducted during REM sleep and as long as these memories are fresh. The effects could be connected to cue-specific arousal responses mediated by the mesencephalic reticular formation (MRF) as later studies of this group showed that MRF stimulation during post training REM sleep, but not during waking or SWS, also enhanced memory though in a different task (6-unit spatial discrimination maze) (535).…”
Section: Reactivating Memories During Sleep By Cueingmentioning
confidence: 84%
“…The delivery of the mild ear-shock was ineffective when the food-shock had been associated with a tone (rather than a mild ear-shock) at training, excluding unspecific effects of stimulus presentation during sleep. Cueing during waking did not affect learning, whereas cueing during SWS and also cueing of old, remote memories during REM sleep acquired 25 days before reduced fear memories (517,518), indicating that cueing of fear memories during sleep strengthen these memories only when cueing is conducted during REM sleep and as long as these memories are fresh. The effects could be connected to cue-specific arousal responses mediated by the mesencephalic reticular formation (MRF) as later studies of this group showed that MRF stimulation during post training REM sleep, but not during waking or SWS, also enhanced memory though in a different task (6-unit spatial discrimination maze) (535).…”
Section: Reactivating Memories During Sleep By Cueingmentioning
confidence: 84%
“…The intensities were varied and delivered in a random order. As in our previous experiments (Hars & Hennevin, 1990;Hars et al, 1985), the chosen intensity induced a slight but reproducible head movement.…”
Section: Methodsmentioning
confidence: 64%
“…In previous experiments, it has been shown that such stimulation can serve as CS in active avoidance conditioning (Hars & Hennevin, 1987;Hars et al, 1985). In a foodreinforced maze-learning task, during which ETS was used as an intratask cue, it has been demonstrated that delivery of ETS in the maze has no effect on learning performance (Hars & Hennevin, 1990). These results show that ETS by itself has no reinforcing power.…”
Section: Second-order Conditioning During Sleepmentioning
confidence: 88%
See 1 more Smart Citation
“…Introducing the cue during SWS impaired retention (Hars & Hennevin, 1987). Most recently, we showed that 1 month after learning, presentation of the cue during PS was still effective in modifying retention performance, but that it had no effect during SWS (Hars & Hennevin, 1990).…”
mentioning
confidence: 91%